Does Camera Use Matter? An Experiment on the Effect of Camera-use on Perceptions of Psychology Students and Lecturers (Innovative Teaching and Learning Journal, 2025)
The Covid-19 pandemic required most of the human population to drastically change their everyday lives to adapt to social distancing. One such change was the rapid migration to online courses which required both students and teachers to quickly adapt to new ways of teaching and learning. Here, we focus specifically on the impact of using online cameras on teaching and learning experiences of university students and lecturers. Through two pre-registered mixed methods studies we observed the impact of using online cameras during an online lecture on students’ (n = 105) and lecturers’ (n = 19) dehumanization, motivation and perceived learning. While quantitative data suggests no significant effect of camera use, qualitative analysis suggests a great impact of camera use, and, more generally of online teaching compared to in-person settings for both lecturers and students. Overall results suggest a nuanced view in which both positive and negative aspects of online teaching are recognized.
Keywords: Online learning; In-person learning; Students; Lecturers; COVID-19